Bulky substituent and solvent-induced alternative nodes for layered Cd-isophthalate/acylhydrazone frameworks - Roztocki, Kornel; Lupa, Magdalena; Hodorowicz, Maciej; Senkovska, Irena; Kaskel, Stefan; Matoga, Dariusz (Crystengcomm, 2018)
A series of three cadmium-based two-dimensional (2D) metal-organic frameworks, featuring 4-pyridinecarboxaldehyde isonicotinoyl hydrazone bridging pillars (pcih) and either 5-tert-butyl-substituted or non-substituted isophthalate linkers, have been prepared and characterized. Isophthalates with bulky tert-butyl substituents (tBu-iso2-) form two-dimensional (2D) frameworks with various metal node nuclearities: [Cd(tBu-iso)(pcih)(DMF)]n or [Cd2(tBu-iso)2(pcih)2]n, dependent on synthetic conditions; whereas, in contrast, unsubstituted isophthalates (iso2-) yield only the framework with dinuclear nodes [Cd2(iso)2(pcih)2]n, regardless of the conditions. Diverse nodes of interdigitated layers have a significant influence on the thermal stability and adsorption behavior of the materials.
CRIS-Team Scopus Importer:2022-04-14